2021
DOI: 10.1371/journal.pone.0246456
|View full text |Cite|
|
Sign up to set email alerts
|

Charged metabolite biomarkers of food intake assessed via plasma metabolomics in a population-based observational study in Japan

Abstract: Food intake biomarkers can be critical tools that can be used to objectively assess dietary exposure for both epidemiological and clinical nutrition studies. While an accurate estimation of food intake is essential to unravel associations between the intake and specific health conditions, random and systematic errors affect self-reported assessments. This study aimed to clarify how habitual food intake influences the circulating plasma metabolome in a free-living Japanese regional population and to identify po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 76 publications
1
14
0
Order By: Relevance
“…Carnosine, a dipeptide also present at high concentrations in muscle tissue, is composed of β-alanine and histidine. Our finding of higher concentrations of 3-methylhistidine and β-alanine after the participants consumed the AP compared to SP diet, during a controlled dietary feeding protocol, is consistent with that observed in two observational studies reporting positive correlations between these two amino acid-related metabolites and meat intake [ 11 , 14 ], in addition to EPIC. Our study design precluded an assessment of the biomarkers that distinguished among red meat, poultry or fish consumption.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Carnosine, a dipeptide also present at high concentrations in muscle tissue, is composed of β-alanine and histidine. Our finding of higher concentrations of 3-methylhistidine and β-alanine after the participants consumed the AP compared to SP diet, during a controlled dietary feeding protocol, is consistent with that observed in two observational studies reporting positive correlations between these two amino acid-related metabolites and meat intake [ 11 , 14 ], in addition to EPIC. Our study design precluded an assessment of the biomarkers that distinguished among red meat, poultry or fish consumption.…”
Section: Discussionsupporting
confidence: 91%
“…The findings indicated that C20:4 carnitine and dimethylglycine were negatively associated, while allantoin, C14:0 sphingomyelin, C38:7 phosphatidyl-ethanolamine plasmalogen, metronidazole, gamma aminobutyric acid and N-methylnicotinate were positively associated with animal protein intake [ 10 ]. Plasma metabolites in a cohort living in Japan found that hydroxyproline, 3-methylhistidine, aromatic amino acids, beta-alanine, carnitine and 2-aminobutyrate were positively associated with animal protein intake [ 11 ]. These studies identified different clusters of animal protein associated metabolites [ 4 , 9 , 10 , 11 ], with amino acids being the main metabolites that differed between dietary animal and plant proteins [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The associations of metabolite levels with extensive food groups have been investigated [67]. Guertin [5] identified a total of 39 serum biomarkers of 36 food groups, such as peanuts with tryptophan betaine, coffee with trigonelline-N-methylnicotinate and quinate, and alcohol with ethyl glucuronide.…”
Section: Food Groupsmentioning
confidence: 99%
“…Metabolic profiling has been used in the fields of medicine, agriculture, plant physiology, and microbiology as a comprehensive, non-targeted approach. Metabolic profiling in food science enables us to evaluate the balance of components in samples, determine the differences in samples containing multi-component compounds, and predict the correlations between bioactivity/functional activity and multi-component compounds [14][15][16]. Recently, Fujimura et al identified multi-component compounds in tea extracts, which Appl.…”
Section: Introductionmentioning
confidence: 99%